Regulation of blood coagulation by the serpin, antithrombin - Olson, Steve (Henry Stewart Talks, 2007)
Antithrombin and hemostasis, Dysfunctional antithrombins and thrombophilia, Protease regulation by serpins, Heparin requirement for antithrombin function, Structural determinants of heparin binding to antithrombin, Heparin-induced conformational changes in antithrombin, Heparin as an allosteric activator of antithrombin, Bridging and conformational change mechanisms of heparin activation of antithrombin, Structural basis of conformational activation, Role of exosites in conformational activation, Role of the reactive loop in antithrombin anticoagulant function, Implications for improved heparin anticoagulants
Archived at 2016/04/27